Two new species of Eucephalobus Steiner, 1936 and one new species of Pseudacrobeles Steiner, 1938 (Rhabditida: Cephalobidae) with mucronate tail (Journal of Nematode Morphology and Systematics, 2012)
Two new species of Eucephalobus and one new species of Pseudacrobeles (Pseudacrobeles) are described from studies by light and scanning electron microscope. Eucephalobus iaculocaudatus sp. n. was collected from decaying tree bark in Puntarenas, Costa Rica. It is characterized by a body length of 424-516 μm in females and 371-407 μm in males, pharyngeal corpus 2.6-3.5 times isthmus length, spermatheca 28-52 μm long, postvulval uterine sac 10-16 μm long, and tail terminus in both sexes bearing a ragged, 2.0-3.5 μm long, mucro having a harpoon-shaped appearance. Eucephalobus asteromucronatus sp. n. was found in grassland soil in Santa Rosa Ecological Reserve, California. It is characterized by a body length of 579-676 μm in females and 573-597 μm in males, pharyngeal corpus 3.0-3.6 times isthmus length, spermatheca 24-40 μm long, postvulval uterine sac 24-32 μm long, tail terminus broadly rounded with a short star-shaped mucro in females and with a ragged, 2.0 μm long, mucro having a brush-like appearance in males. Pseudacrobeles (P.) maungatautariensis sp. n. was found associated with epiphyte vegetation in Maungatautari Reserve, New Zealand. It is characterized by a body length of 585-768 μm in females and 551-613 μm in males, pharyngeal corpus 4.1-5.8 times isthmus length, spermatheca 32-63 μm long, postvulval uterine sac 41-67 μm long, and tail terminus with a ragged, 3.0 μm long, mucro in females and with a ragged, sharply pointed, 4.0-5.0 μm long mucro in males